Effect of Technology Acceptance on Student Commitment in Turkish Higher Education - Yunus Doğan; Coşkun Akça (Journal of Learning for Development)
There is strong evidence in the relevant literature that the use of technology in higher education positively affects academic achievement and motivation. However, while there are some international studies on the effect of technology acceptance on college student commitment, it is understood that there has not been enough research in the national literature on this topic. In this context, this study aims to examine the effect of college students' tendencies toward using digital technology on student commitment. This research was conducted with a total of 321 Turkish college students and data were collected using the Student Commitment Scale in Higher Education developed by Çınkır et al. (2021) and the Tendency Scale for Using Technology in Class developed by Günüç and Kuzu (2014). The research revealed that college students generally have a favorable attitude (3.96) and inclination (3.82) towards using digital technology during classes, alongside a moderate level of dedication (3.42) to their university. Additionally, it was discovered that students who are highly committed to their higher education also tend to use digital technology more in classrooms. Notably, the analysis indicates that around 12% of the variance in college students' commitment to higher education can be explained by their inclination towards digital technology use. This emphasises the significance of integrating digital tools in educational settings, as it appears to positively influence students' engagement and commitment to their studies.